Yield, production cost and incidence of club root disease of crucifers under soil fertility management practices using various combinations of soil additives - Cuevas, Virginia C.; Bul-long, Mar S. (2009)
Three methods of reducing club root disease incidence - UPLB Method I, UPLB Method II (involving an integrated disease management approach through the use of various soil additives) and Farmers' Practice (FP) - were evaluated in seven barangays of Buguias, Benguet by farmers on cabbage (Brassica oleracea, capitata group) and wombok or Chinese pechay (Brassica rapa, Pekinensis group) as test crops. UPLB M I and M II were both tested by 10 randomly selected cabbage farmers and FP by eight other randomly selected farmers. Three randomly selected wombok farmers tested both M I and M II and three other wombok farmers the FP method. Method I used 0.13 kg m -2 lime, 0.09 kg m -2 triple 14 chemical fertilizer, 0.525 kg m -2 chicken manure, 0.54 mL m -2 chemical insecticide and 3 g m -2 Trichoderma spp. biocon powder inoculant applied at seed bed. UPLB M II used 0.13 kg m -2 lime, 0.06 kg m -2 triple 14 chemical fertilizer, 0.35 mL m -2 chemical insecticide, compost applied at 0.6 kg m -2 prepared from crop residues - weeds mixed with 0.358 kg m -2 chicken manure, and 3 g m -2 Trichoderma spp. biocon powder inoculant applied at seed bed. FP used 0.14 kg m -2 triple 14 chemical fertilizer, 1.57 kg m -2 chicken manure, 2.35 g m -2 chemical fungicide and 1.7 mL m -2 chemical insecticide. At harvest, mean disease incidence in cabbage for UPLB Methods I and II was 2% and 1%, respectively, and 26% for FP. In wombok, it was 4.6% and 3.4%, respectively, for UPLB Methods I and II and 23% for FP. Partial production cost per kg of cabbage (farm gate) for UPLB Method I was PhP 1.53, PhP 1.49 for UPLB Method II and PhP 4.75 for FP. In wombok (farm gate), it was PhP 1.31 for UPLB Method I, PhP 1.21 for UPLB Method II and PhP 4.55 for FP. Mean weight per head in UPLB Methods I and II was the same at 1 kg and 2.0 kg while that of FP was 0.75 kg and 0.81 kg for cabbage and wombok, respectively. Mean differences were significant based on t-test comparison of M I vs. M II, FP vs. M I and FP vs. M II for the tested parameters.
Keywords: Plant diseases; Soil fertility; Cabbage